Board characteristics and corporate social responsibility disclosure in the jordanian banks - Norsiah, Ahmad; Mohammad Ahid, Ghabayen; Nor Raihan, Mohamad (Virtus Interpress, 2016)
This paper aims to examine the impact of board characteristics on the level of corporate social responsibility disclosure (CSRD) in the Jordanian banking sector for a sample of 147 banks/years during a period of 10 years (2004-2013). A checklist consisting of 100 items is developed to measure the disclosure level and the result indicates a relatively low level of disclosure in Jordanian banks. Multiple regression analysis is employed to examine the developed hypotheses. The results indicated that the larger board size and higher level of disclosure are correlated. However, low level of disclosure is associated to higher proportion of independent directors and institutional directors. In addition, female director is found to negatively affect the level of disclosure. This study has filled some of the previous studies’ gaps; the study is conducted in a new business environment. Besides, previous CSRD’s studies have not considered some of the board characteristics such as institutional directors. Thus this study investigates their impacts on the level of CSRD. In addition, this study provides some guidelines for the future works. Furthermore, the findings of this study might be interested to several groups of shareholders and stakeholders such as government, regulators, potential investors and CSR agencies.